2019
DOI: 10.15408/tazkiya.v7i2.13473
|View full text |Cite
|
Sign up to set email alerts
|

Optimisme dan Dukungan Sosial terhadap Self-Efficacy Anak Jalanan

Abstract: The study aims to determine whether there is a link between optimism and social support for self-efficacy in street children. 103 adventure samples of street children taken from seven open houses spread in DKI Jakarta and Tangerang. This study uses a non-probability sampling technique, using a purposive sampling method. Test the validity of measuring instruments using confirmatory factor analysis (CFA) techniques, while the data analysis in this study uses multiple regression analysis techniques in SPSS. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Alat ukur yang digunakan untuk mengukur kepercayaan diri (X1) adalah Self Confidence Scale lauster yang dikembangkan oleh Krisphianti (2020), untuk alat ukur variabel dukungan sosial teman sebaya adalah social support scale Sarafino yang dikembangkan oleh Sukasari (2017), skala optimisme menggunakan optimsm scale yang mengacu pada teori martin Seligman yang dikembangkan oleh Adityawarman (2019). Semua skala yang digunakan sebelumnya sudah melewati prosedur penyusunan skala mulai dari pembuatan item sampai dengan pengujian properti psikometris skala atau alat ukur tersebut.…”
Section: Metodeunclassified
“…Alat ukur yang digunakan untuk mengukur kepercayaan diri (X1) adalah Self Confidence Scale lauster yang dikembangkan oleh Krisphianti (2020), untuk alat ukur variabel dukungan sosial teman sebaya adalah social support scale Sarafino yang dikembangkan oleh Sukasari (2017), skala optimisme menggunakan optimsm scale yang mengacu pada teori martin Seligman yang dikembangkan oleh Adityawarman (2019). Semua skala yang digunakan sebelumnya sudah melewati prosedur penyusunan skala mulai dari pembuatan item sampai dengan pengujian properti psikometris skala atau alat ukur tersebut.…”
Section: Metodeunclassified
“…Dhio Adityawarman has conducted previous research on 103 street children in the DKI Jakarta region, which showed that the contribution of optimism toward the selfefficacy of street children was 72.9% (Adityawarman, 2019). Having a sense of optimism can also affect confidence in students' abilities.…”
Section: Introductionmentioning
confidence: 99%